1999
DOI: 10.1093/nar/27.18.3660
|View full text |Cite
|
Sign up to set email alerts
|

The 5'-untranslated region of GM-CSF mRNA suppresses translational repression mediated by the 3' adenosine-uridine-rich element and the poly(A) tail

Abstract: Granulocyte-macrophage colony stimulating factor (GM-CSF) mRNA levels are controlled post-transcriptionally by the 3'-untranslated region (UTR) adenosine-uridine-rich element (ARE). In untransformed, resting cells, the ARE targets GM-CSF mRNA for rapid degradation, thereby significantly suppressing protein expression. We used a rabbit reticulocyte lysate (RRL) cell-free system to examine translational regulation of GM-CSF expression. We uncoupled decay rates from rates of translation by programming the RRL wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Blocking of ARE-mediated mRNA decay because translation initiates from an IRES suggests that the ARE-destabilizing function may be linked to events occurring at the 5Ј-end of the transcript, such as decapping. This is in accordance with recent data reported in mammalian cells, where the ARE stimulated decapping in HeLa cell extracts (7), and in vitro experiments, where the GM-CSF 5Ј-UTR was able to suppress the translational repression mediated by the GM-CSF ARE located in the 3Ј-UTR (9). Concerning this last point, we performed cell transfections with a plasmid containing both GM-CSF 5Ј and 3Ј-UTRs and repeated our analysis of EGFP expression by flow cytometry and Western and Northern blots.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Blocking of ARE-mediated mRNA decay because translation initiates from an IRES suggests that the ARE-destabilizing function may be linked to events occurring at the 5Ј-end of the transcript, such as decapping. This is in accordance with recent data reported in mammalian cells, where the ARE stimulated decapping in HeLa cell extracts (7), and in vitro experiments, where the GM-CSF 5Ј-UTR was able to suppress the translational repression mediated by the GM-CSF ARE located in the 3Ј-UTR (9). Concerning this last point, we performed cell transfections with a plasmid containing both GM-CSF 5Ј and 3Ј-UTRs and repeated our analysis of EGFP expression by flow cytometry and Western and Northern blots.…”
Section: Discussionsupporting
confidence: 93%
“…However, in their report, Jarzembowski et al (9) show that the GM-CSF ARE could specifically inhibit translation of a polyadenylated transcript independently of its effect on the mRNA decay. Our in vivo results support these in vitro results since we showed that EGFP expression initiated by either cap-or IRES-dependent translation is dramatically inhibited by the GM-CSF ARE, whereas ARE-containing EGFP mRNAs persisted in the cells (Figs.…”
Section: Discussionmentioning
confidence: 93%
“…ment (nucleotides numbered 137-152 in figure 8), which is similar to AU-rich elements found to participate in translation repression of several other mRNAs (e.g. granulocyte-macrophage colony-stimulating factor [50], p53 [51],TNF-· [52], or Vg1 [53]). We used the m-fold program of Zuker and colleagues [54] to show that CKB 3) UTR can be folded into two classes of configuration each with considerable stability (approximately -60 kcal/mol; fig.…”
Section: Discussionmentioning
confidence: 91%
“…Because other regulatory sequences located within the mRNA could influence ARE activity, we kept in the constructs the ARE in its natural context. 15,16 Moreover, to analyze when and where the ARE controls the level of GM-CSF mRNA expression, the constructs were placed under the transcriptional control of the cytomegalovirus (CMV) early immediate promoter, which has been shown to be active early in development and in most tissues. 17,18 Because both constructs led to major lethality before birth, we analyzed transgene expression during late embryonic development.…”
Section: Introductionmentioning
confidence: 99%